Theodoric's rainbow - Kramer, Stephen P.; Duffy, Daniel M (New York : Scientific American Books for Young Readers, 1995)
Theodoric of Freiberg, a Dominican friar of the early fourteenth century, discovers how sunlight and drops of water make rainbows.
Keywords: Dietrich, -- von Freiberg, -- ca. 1250-ca. 1310 -- Juvenile fiction; Dietrich, -- von Freiberg, -- ca. 1250-ca. 1310 -- Fiction; Rainbows -- Fiction; Friars -- Fiction